Neurogenic Bowel Dysfunction - Krogh, Klaus (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Disorders of the central and peripheral nerve systems have severe effects on gut function. Hence, people who have sustained spinal cord injury and multiple sclerosis, Parkinson's disease, or spina bifida patients may suffer from severe bowel symptoms, including constipation, incontinence to stools, difficult bowel evacuation, or pain. For the present book, a number of international experts have described how disorders of the nerve system affect bowel function, how to assess and treat bowel symptoms, and how the bacterial composition of the bowel may be affected.